2021
DOI: 10.3201/eid2711.211886
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of BNT162b2 Vaccine in Adolescents during Outbreak of SARS-CoV-2 Delta Variant Infection, Israel, 2021

Abstract: I n May 2021, the US Food and Drug Administration and the European Medicines Agency expanded existing authorization for BNT162b2 vaccine (Pfi zer-BioNTech, https://www.pfi zer.com) against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to include its use in adolescents 12-15 years of age (1,2). On June 2, 2021, the Israel Ministry of Health declared the availability of BNT162b2 vaccine for adolescents 12-15 years of age (3) as a 2-dose regimen, given 21 days apart. By August 26, 2021, a total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 7 publications
5
63
0
2
Order By: Relevance
“…Evidence among adolescents on vaccine effectiveness against Covid-19 in real-world settings are limited. A nationwide retrospective cohort study from Israel on vaccine effectiveness of BNT162b2 in adolescents during SARS-CoV-2 delta variant outbreak showed 91.5% (95% CI 88.2–93.9%) post two-dose vaccination [7] . In a test-negative, case-control study at U.S. pediatric hospitals, the effectiveness of 2 doses of BNT162b2 against Covid-19 hospitalization in children and adolescents aged 12-18 years was 93% (95% CI, 83-97) [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence among adolescents on vaccine effectiveness against Covid-19 in real-world settings are limited. A nationwide retrospective cohort study from Israel on vaccine effectiveness of BNT162b2 in adolescents during SARS-CoV-2 delta variant outbreak showed 91.5% (95% CI 88.2–93.9%) post two-dose vaccination [7] . In a test-negative, case-control study at U.S. pediatric hospitals, the effectiveness of 2 doses of BNT162b2 against Covid-19 hospitalization in children and adolescents aged 12-18 years was 93% (95% CI, 83-97) [8] .…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 Vaccine efficacy against Covid-19 from 7 days to 6 months after the second dose was 91%, 6 with a similar estimated real-world effectiveness from 8 to 28 days after the second dose. 7 …”
mentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID- 19), caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is responsible for the most recent global pandemic, declared by the World Health Organization (WHO) on 11 March 2020 [1]. COVID-19 is a serious illness that has had a significant impact on public health due to its high morbidity and mortality rates [2].…”
Section: Introductionmentioning
confidence: 99%
“…The recent surge in cases despite extensive vaccination campaigns supports the concern about low vaccine effectiveness against variants. Studies are at odds regarding this topic, with some claiming that breakthrough infections are more likely to occur due to viral escape from antibodies [11,12]; others have demonstrated that mRNA vaccines remain effective through limiting COVID-19 severity, hospitalization and deaths [13][14][15][16][17][18][19][20][21]. Recently, more studies are exploring the efficacy of the natural immune response to SARS-CoV-2 vs. the mRNA vaccine-elicited response [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%